A common deletion in the growth hormone receptor gene (d3-GHR) in the offspring is related to maternal placental GH levels during pregnancy. (December 2020) - Jensen, Rikke Beck; Boas, Malene; Nielsen, John E.; Maroun, Lisa Leth; Jørgensen, Anne; Larsen, Torben; Main, Katharina M.; Juul, Anders
Abstract: Background: A common growth hormone receptor polymorphism with deletion of exon 3 (d3-GHR) has previously been linked to increased postnatal growth on the one hand and decreased fetal growth on the other. Regulation of fetal growth is positively dependent on secretion of placental GH (hGH-V). Objective: We explored the effect of the fetal d3-GHR genotype on maternal serum levels of hGH-V and fetal growth. The cellular localization of hGH-V synthesis and the GH receptors were determined in normal placentas. Methods: 43 healthy mother-child pairs were examined during pregnancy with measurements of hGH-V during third trimester, and serial ultrasound measurements determined fetal growth rate. Birth anthropometrics were obtained. The GHR genotype of the child was analysed postnatally. Immunohistochemical (IHC) analysis was conducted on four placentas. Results: The presence of the d3-GHR genotype was associated with a markedly reduced concentration of hGH-V in maternal serum (β −0.52, SE 0.24, p  = 0.04) compared to those who had a fl/fl genotype. Accordingly, a tendency towards reduced fetal growth rate during third trimester (β −25.8, SE 12.7, p  = 0.05) and a lower birth weight were found among carriers of the d3-GHR allele, but these associations did not reach statistical significance ( p  = 0.08). IHC analysis showed expression of placental GH and GHR in the villous syncytiotrophoblast, the extravillous trophoblast, and the decidual cells and smooth muscle cells in chorionic vessels. Conclusions: The presence of the d3-GHR polymorphism in the fetus was associated with lower maternal serum levels of hGH-V, decreased fetal growth rate in third trimester and lower birth weight compared to the wildtype. Highlights: A common polymorphism in the growth hormone receptor gene was associated with lower placental growth hormone. Fetal growth and birth weight was decreased in children with a common polymorphism in the growth hormone receptor gene. Placental growth hormone (GH) and GH receptor were found in the villous syncytiotrophoblast and the extravillous trophoblast.